Thomas Pryce-Davies interviewed by Carole Ottway for the Australia 1938 oral history project - Pryce-Davies,Thomas, 1921-2008.; Ottway, Carole; Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1982)
Thomas speaks of his family's home; living conditions; school and childhood memories; recreation; family life; experiences at teachers college; teaching experiences; local area and community of Goodna, Queensland.
Recorded by the Australia 1938 Oral History Project as research for the book Australians, a historical library.
Recorded on 21 September 1982.
Digital master available
Time-coded summary available.
Full transcript unavailable interview summarised (6 p.)
Keywords: Pryce-Davies, Thomas, -- 1921-2008 -- Interviews; Teachers -- Queensland -- Biography; Goodna (Qld.) -- Social conditions